Let's Turn Your Smart Phone to a Smart Physician - Karthik Anantharaman (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Your  smart phone can do many things. Can it be a doctor, too? Absolutely yes, with BPL Medical Technologies Private Limited introducing BPL LifePhone PlusTM, a revolutionary all-in-one health monitoring device, which can transform your smart phone to your family doctor. The burden of cardiovascular diseases is rising steadily in both emerging and emerged economies and the number of patients undergoing medical & surgical intervention for cardiovascular diseases is also on the rise. In addition, many patients with cardiovascular diseases also have diabetes. Routine monitoring of the clinical parameters in these patients becomes pertinent to assess disease control and prognosis in these patients.